Allopregnanolone and neurogenesis in the nigrostriatal tract - Wang, Jun Ming (Frontiers in Cellular Neuroscience, 2014)
Reinstalling the neurobiological circuits to effectively change the debilitating course of neurodegenerative diseases is of utmost importance. This reinstallation requires generation of new cells which are able to differentiate into specific types of neurons and modification of the local environment suitable for integration of these new neurons into the neuronal circuits. Allopregnanolone (APα) seems to be involved in both of these processes, and therefore, is a potential neurotrophic agent. Loss of dopamine neurons in the substantia nigra (SN) is one of the main pathological features of Parkinson’s and also in, at least, a subset of Alzheimer’s patients. Therefore, reinstallation of the dopamine neurons in nigrostriatal tract is of unique importance for these neurodegenerative diseases. However, for the neurogenic status and the roles of allopregnanolone in the nigrostriatal tract, the evidence is accumulating and debating. This review summarizes recent studies regarding the neurogenic status in the nigrostriatal tract. Furthermore, special attention is placed on evidence suggesting that reductions in allopregnenalone levels are one of the major pathological features in PD and AD. This evidence has also been confirmed in brains of mice that were lesioned with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) or those bearing neurodegenerative mutations. Lastly, we highlight studies showing that allopregnanalone can augment the number of total cells and dopaminergic neurons via peripheral exogenous administration.